Kombinasi Mode Cipher Block Chaining Dengan Algoritma Triangle Chain Cipher Pada Penyandian Login Website - Lombu, Dafirius; Tarihoran, Siska Dame; Gulo, Irwan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Generally, the database access of a website lies in the user login. When the login data is not accompanied by security techniques, it is very easily accessible by other parties. One effort that can be done to solve the problem is to encode the login data of website users based on cryptographic technique algorithm. Triangle Chain Cipher (TCC) is one of the classic cryptographic algorithms that encode data doubly and generate keys randomly along the plain. The process of encryption and decryption are interdependent to be one of the advantages of this algorithm. This algorithm will be more effective when combined with the Cipher Block Chaining (CBC) operation mode that is widely used in modern cryptographic algorithms today. The feedback mechanism between the blocks in this mode of operation is the operating advantage. This study describes how to combine the mode of operation of block chaining cipher with triangle chain cipher algorithm so that cipher data login website generated more random and difficult to find its original meaning.